O Instituto da Memória do Povo Cearense (IMOPEC): entre experiências educativas e a defesa de direitos, da cultura e do patrimônio cultural (1988-2015) - Sales, Ana Cristina de (2023)
The thesis aimed to understand the educational experience organized and developed by the Instituto da Memória do Povo Cearense (IMOPEC) between 1988 and 2015, problematizing the actions and the struggles pursued by the institution, in order to provide a new meaning to memory and cultural heritage through social movements. The text was developed based on reflections on Social History, dialoguing with the concepts of Popular Education, Social Memory, Cultural Heritage and Social Movements. The research was developed using written and oral sources. In relation to written sources, the following stood out the Raízes bulletin and the Propostas Alternativas magazine, printed information vehicles, published by the Institute as a combat pedagogical instrument. The material from the oral narratives was prepared through the arts of listening and relationships with people who participated in the Institution, including founding partners and members of the Distance Learning Course “Memory and Cultural Heritage of Ceará.” The study indicated that the Institute produced a series of materials, recorded in bulletins, magazines, photos, videos, booklets, inventories, and catalogues. These materials emerged in response to the need to publicize proposals and questions about Ceará and its communities. Through these records, IMOPEC sought to promote the protagonism of various subjects by giving them the opportunity to narrate their stories and insert them into the history of Ceará. In this way, the institution asserted itself as a voice denouncing social and cultural aggressions, directing its discourse towards strengthening the struggles of the various actors forgotten by the historiography of Ceará. Thus, IMOPEC demonstrated itself as a political collective, coming from different social movements under a strong, integral and diligent leadership and constituted itself as an Institute to provoke, associate and act with social strata affected by actions of neoliberal governments in the decades of 1990-2000 that significantly changed their forms of life and sociability, whether in terms of heritage and/or environmental issues.